Deep-sea environments across the Cretaceous/Paleogene boundary in the SE Atlantic Ocean (ODP Leg 208 Hole 1262C, Walvis Ridge) - Alegret, Laia; Thomas, Ellen (Anuário do Instituto de Geociências, 2006)
Abstract